Soft medical robotics: clinical and biomedical applications, challenges, and future directions. (2nd November 2019) - Hsiao, Jen-Hsuan; Chang, Jen-Yuan (James); Cheng, Chao-Min
ABSTRACT: Bioinspired soft robotics allow for safer clinical interactions with human patients but conventional, hard robots, which are often built with rigid materials and complex control systems, compromise tissue integrity, freedom of movement, conformability, and overall human bio-compatibility. Soft, compliant materials intrinsically reduce mechanical complexity, accommodate their usage environment, and provide great practical potential for medical device developments. Previous review papers have generally covered the topics of materials, manufacturing processes, actuator modeling and control, and current trends. Here, we focus on recent developments in soft robotic applications for the medical field including advances in cardiac devices, surgical robots, and soft rehabilitation and assistance devices. In medical applications, soft robotic devices not only expedite the evolution of minimally invasive surgery but also improve the bio-compatibility of rehabilitation and assistance devices. Here, we evaluate design requirements, mechanisms, achievements and challenges in these key areas. Of particular note, this paper concludes with a discussion on advances in 3D printing and adapting neural networks for modeling and control frameworks that have facilitated the development of faster and less expensive soft medical devices. GRAPHICAL ABSTRACT: